Green transformational leadership as a foundation for implementing green strategic orientations and the development of green innovation and green performance - Manuel Alejandro Ibarra-Cisneros; Juan Benito Vela-Reyna; Felipe Hernández-Perlines (Entrepreneurial Business and Economics Review (EBER), 2024)
Objective: The objective of the article is to examine the influence of green transformational leadership on green entrepreneurial and green market orientations, which, in turn, affect green innovation. Moreover, the article analyses the relationship between green innovation and green performance. Research Design & Methods: We used a quantitative research design. We applied a 37-item survey to a sample of 398 small, medium, and large companies in the industrial and service sectors of Mexico. We analysed the results using the partial least squares structural equation modelling approach. Findings: Green transformational leadership has a strong influence on green entrepreneurial and green market orientation. Besides, only green entrepreneurial orientation positively influences green innovation. Finally, there is a relationship between green innovation and green performance. Implications & Recommendations: Theoretical implications support most of the arguments put forth in various studies. However, the context can modify the behaviour of the studied relationships. The results provide arguments for adopting a sustainable view of activities within organisations, leading to improved performance and the achievement of competitive advantages. Contribution & Value Added: The main contribution of this article is that it demonstrates the importance of green transformational leadership as an element that allows the development of green entrepreneurial orientation and green market orientation, which stimulate green innovation. Likewise, the context does influence the behaviour of the observed variables.
Keywords: L25; M14; 330; green transformational leadership; strategic orientations; green innovation; perfor-mance; companies